Динамика эндотелиальной дисфункции под воздействием нитратной нагрузки = Dynamics endothelial dysfunction nitrate under the influence of load - I. V. Savitskiy; T. B. Gorbach; I. V. Miastkovskaja; P. E. Grigoriev; E. Yu. Yakushkin; A. A. Sliusar (Kazimierz Wielki University, 2016)
Savitskiy I. V., Gorbach T. B., Miastkovskaja I. V., Grigoriev P. E., Yakushkin E. Yu., Sliusar A. A. Динамика эндотелиальной дисфункции под воздействием нитратной нагрузки = Dynamics endothelial dysfunction nitrate under the influence of load. Journal of Education, Health and Sport. 2016;6(2):337-348. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55401 http://ojs.ukw.edu.pl/index.php/johs/article/view/3576   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.   ДИНАМИКА ЭНДОТЕЛИАЛЬНОЙ ДИСФУНКЦИИ ПОД ВОЗДЕЙСТВИЕМ НИТРАТНОЙ НАГРУЗКИ   1И. В. Савицкий, 2Т. В. Горбач, 1И. В. Мястковская, 3П. Е. Григорьев, 1Е. Ю. Якушкин, 1А. А. Слюсарь   Одесский национальный медицинский университет, Одесса, Украина1 Харьковский национальный медицинский университет, Харков, Украина2 Физико-технический институт, ФГАОУ ВО «КФУ им. В.И. Вернадского», Симферополь3   Резюме Цель данного исследования - исследование следующего ряда маркеров выбора: малонового диальдегида, каталазы, супероксиддисмутазы, ассиметрического диметиларгинина, L-аргинина, нитрозатиолов, суммы эндогенных нитратов и нитритов. Результаты: 1. Хроническая нитратная интоксикация приводит к развитию окислительного стресса, о чем свидетельствуют  резкое повышение уровне малонового диальдегида при недостаточной активации супероксиддисмутазы и каталазы, которые являются ферментами антиоксидантной защиты. 2. Значительно снижена продукция оксида азота, о чем свидетельствует уменьшение содержания нитрозатиолов и суммы нитратов и нитритов. В группе с применением L-аргинина отмечается субкомпенсация уровня нитрозотиолов и суммы эндогенных нитратов и нитритов. Снижение уровня отмечается, но менее выражено. 3. Отмечается увеличение уровня ассиметричного диметиларгинина, что является следствием влияния окислительного стресса и еще одним фактором, подтверждающим возникновение эндотелиальной дисфункции на фоне хронической нитратной нагрузки. 4. Выявлена взаимосвязь между уровнями АДМА, индуцибельной NO-cинтазы и L-аргинина. 5. Подтверждается ранее выявленное нами защитное воздействие L-аргинина на сосуды при хроническом нитратном воздействии.   Ключевые слова: эндотелиальная дисфункция, нитратная нагрузка, L-аргинин.   DYNAMICS endothelial dysfunction nitrate UNDER THE INFLUENCE OF LOAD   1I. V. Savitskiy, 2T. B. Gorbach, 1I. V. Miastkovskaja, 3P. E. Grigoriev, 1E. Yu. Yakushkin, 1A. A. Sliusar   Odessa National Medical University, Odessa, Ukraine1 Kharkiv National Medical University, Kharkiv, Ukraine2 V. I. Vernadsky Crimean Federal University, Simferopol3   Summary The purpose of this research was to study the next series of markers of choice: malondialdehyde, catalase, superoxide dismutase, asymmetric dimethylarginine, L-arginine, nitrosothiols, the complex of endogenous nitrates and nitrites. Results: 1. The chronic nitrate intoxication leads to the development of oxidative stress, as evidenced by a sharp increase in the level of malondialdehyde in case of insufficient activation of superoxide dismutase and catalase, which are antioxidant enzymes. 2. Greatly reduced production of nitric oxide, as demonstrated by decrease in amount nitrosothiols and nitrates and nitrites. In the group using L-arginine levels observed endogenous subcompensation of nitrosothiols, nitrates and nitrites. The decrease was noted, but less expressed. 3. The increase levels of asymmetric dimethylarginine were noted, which is a result of oxidative stress and is another factor confirming the endothelial dysfunction in chronic nitrate load. 4. The correlation between the levels of ADMA, inducible NO-cintazy and L-arginine was revealed. 5. The earlier determined protective effect of L-arginine on blood vessels in chronic nitrate exposure was confirmed.   Key words: endothelial dysfunction, nitrate load, L-arginine.